A Teologia do Cordeiro no Evangelho segundo João: Jo 1,29;19,34-36 - Nascimento, Abimael Francisco do (2013)
This research was guided by the method of literature review, in order to answer the question put on the problem: Which is the relevance and which are the implications of the image of the lamb, attributed to Jesus in the Gospel of John? - This question raises some considerations, such as: the relevance occurs due to the formation of the community that is the basis of this Gospel, as to say, groups that formed the Johannine community, those of the first hour, knew the cultic life of the Israelite tradition and applied it to Jesus through the typology of the lamb. A second consideration is that the lamb was in the worship, either to Jews or Samaritans, an element very present, kept from thanksgiving to the atonement. However, their presence more fixed in memory was that linked to the night of the Exodus, in which God commanded to sacrifice a paschal lamb. This celebration reminded every year the divine intervention and cherished the hope of a new exodus, in which the people would be released from the judge of the empires. The third consideration is on the figure of the lamb and the prophetic tradition of the Second Isaiah, who had proposed a cultic replacement: now a servant, like a lamb, would be the atoning of the sins of the people ( cf. Is 53:7 ). The servant of Isaiah takes the atoning function, something that was reserved for sacrificial rituals. Now, the servant assumes this function. Given this, the salutation of John the Baptist to Jesus (cf. Jn 1:29 ) gains another dimension, but with the possibility of combining the two ideas, as to say, the greeting of the Batista seems to address both perspective of the Paschal Lamb as well as the Suffering Servant. So that the Johannine Jesus assumes the role of lamb, but no more a lamb only to Israel but to the whole world. With this, the salvation of the Lamb-Servant is universal. He plays the role of forgiving sins and to make passing to eternal life, since He reconciles the mankind to God through his blood. The greeting of John the Baptist in John 1:29, in principle shows somewhat understandable, however, from a theological journey that culminates on Golgotha, in John 19.34-36, it is understandable what John the Baptist had announced in the opening week of Jesus' activity. Now, in the Passion, the final Easter is accomplished, full forgiveness is given, through the voluntary surrender of the Lamb of God